2022
DOI: 10.3390/su14084690
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Contaminants in Watercress (Nasturtium officinale R. BR.): Toxicity and Risk Assessment for Humans along the Swat River Basin, Khyber Pakhtunkhwa, Pakistan

Abstract: This research aimed to investigate the bioaccumulation and health risk associated with absorption of the selected heavy metals (HMs) i.e., lead (Pb), cadmium (Cd), zinc (Zn), and copper (Cu) in a wild leafy vegetable Nasturtium officinale that grows along the Swat River in swampy areas. The areas were categorized using the ecological risk index (RI), which indicates how heavy metal concentrations in soil and plants change over time. The bioaccumulation factor was greater than that at the 400 ≤ RI sites, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Whereas we detected no obvious anomaly (any significant high value) in the distribution of Cu near urban areas, the distributions of Hg, Cd, and Pb have clearly been influenced to varying extents by the human activities in urban areas and the quarrying of building stone. This view is consistent with the conclusion of Khan N et al [65] on heavy metals in soils along the Swat River Basin, Khyber Pakhtunkhwa, Pakistan. Specifically, in the granite-rich region to the north of the study area, we obtained notably low values for As and Pb, whereas Cd, Cr, Hg, and Ni showed mixed distribution patterns of low and medium-high abundance.…”
Section: Correlation and Spatial Distribution Of Heavy Metalssupporting
confidence: 92%
“…Whereas we detected no obvious anomaly (any significant high value) in the distribution of Cu near urban areas, the distributions of Hg, Cd, and Pb have clearly been influenced to varying extents by the human activities in urban areas and the quarrying of building stone. This view is consistent with the conclusion of Khan N et al [65] on heavy metals in soils along the Swat River Basin, Khyber Pakhtunkhwa, Pakistan. Specifically, in the granite-rich region to the north of the study area, we obtained notably low values for As and Pb, whereas Cd, Cr, Hg, and Ni showed mixed distribution patterns of low and medium-high abundance.…”
Section: Correlation and Spatial Distribution Of Heavy Metalssupporting
confidence: 92%
“…However, the results of this study were approximately 2 times higher than those results. In Pakistan, Cd levels ranging from 0.02 to 0.05 were found from the consumption of watercress green vegetables grown in swampy areas, all of which were lower than this present results (Khan et al, 2022). The HQ values of Pb exposure rates were in the following order in the adult population: 0.14 for GO, 0.12 for RC, and 0.10 for CL.…”
Section: Lead (Pb) Exposure Via Leafy Vegetables Ingestioncontrasting
confidence: 78%
“…The synthesis of N α -acetyl-S-(N-phenethylthiocarbamoyl)-glutathione (PEITC-NAC conjugate; the end-product of PEITC metabolism through the mercapturic acid pathway) produced a good yield, while its purity was assessed via UPLC-MS/MS (Figure S1), 1 H-(Figure S2A) and 13 C-NMR (Figure S2B).…”
Section: Synthesis Of Phenethyl Isothiocyanate-n-acetyl Cysteine Adductmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https://www.mdpi.com/article/10.3390/antiox13010082/s1, Figure S1: Mass spectrum of the synthesized PEITC-NAC conjugate. Figure S2: 1 H-NMR (A) and 13 C-NMR (B) spectra of N α -acetyl-S-(N-phenethylthiocarbamoyl)-glutathione at 500 MHz and 100 MHz in DMSO-d 6 respectively. Table S1: Multiple reaction monitoring conditions for N α -acetyl-S-(N-phenethylthiocarbamoyl)glutathione in UPLC-MS/MS analysis.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation